PENERAPAN TEKNOLOGI NATURAL USER INTERACE (NUI) SEBAGAI STRATEGI PEMBELAJARAN TERHADAP RETENSI BELAJAR - Citra Kurniawan (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2017)
This study explains the use of the Natural User Interface (NUI) on retention of learning. The combination of multimedia and virtual reality is called immersive multimedia. Immersive multimedia is the reality of computer simulations that replicate the environment resulting in user interaction. Immersive multimedia technology is applied to natural user interface (NUI). Natural user interface (NUI) has great potential to facilitate new ways of computer-based learning. The result of instructional media development in this research is an interactive learning media that allows learners to display presentation content and manipulate presentation content directly so as to stimulate visual which improves learning retention. Key Word: Natural User Interface (NUI), Educational, Retention, Immersive Multimedia, Interactive Learning